2023
DOI: 10.1103/physrevmaterials.7.024405
|View full text |Cite
|
Sign up to set email alerts
|

Confined spin waves in magnetochiral nanotubes with axial and circumferential magnetization

Abstract: We report experimental studies of spin-wave excitations in individual 22 nm thick Ni80Fe20 nanotubes with diameters of about 150 nm. We apply Brillouin light-scattering (BLS) spectroscopy under microwave irradiation and resolve sets of discrete resonances in the center of nanotubes ranging from 2.5 to 12.5 GHz. Comparing to a recent theoretical work and micromagnetic simulations, we identify different characteristic eigenmodes depending on the axial, mixed or vortex configuration. The mixed and vortex states g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…[51] In Ref. [39], it has been shown that individual nanotubes with unintentional defects exhibit a multitude of resonant modes due to two discretization effects. On the one hand, spin waves undergo constructive interference along the azimuthal direction.…”
Section: Discrete Surface Magnon Modes In the Top-layer Of A 3d Ni Na...mentioning
confidence: 99%
See 3 more Smart Citations
“…[51] In Ref. [39], it has been shown that individual nanotubes with unintentional defects exhibit a multitude of resonant modes due to two discretization effects. On the one hand, spin waves undergo constructive interference along the azimuthal direction.…”
Section: Discrete Surface Magnon Modes In the Top-layer Of A 3d Ni Na...mentioning
confidence: 99%
“…Further BLS experiments were performed on a bare polymer woodpile structure, which showed the same mode independent of magnetic field. Hence, this mode does not have a magnetic origin.In the following, we discuss the three field-dependent modes and compare them to magnon modes recently reported for straight and long nanotubes [39]. For this, we classified the extracted resonance frequencies into different branches (red, green, and purple symbols in Figure2a).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The field of magnetic nanotube synthesis has yielded a wide variety of materials that have been successfully utilized in the creation of these structures. Among the most commonly synthesized magnetic nanotubes are those made from materials such as iron (Fe) [ 8 , 9 ], Fe(OH) 3 [ 10 ], maghemite (γ-Fe 2 O 3 ) [ 10 , 11 , 12 ], magnetite (Fe 3 O 4 ) [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], ZnFe 2 O 4 [ 19 ], CuFe 2 O 4 [ 20 ], nickel (Ni) [ 8 , 21 , 22 , 23 ], NiFe 2 O 4 [ 24 ], Ni 64 Fe 36 [ 8 ], Ni 80 Fe 20 (permalloy) [ 25 ], Co [ 8 , 23 , 26 ], Co 3 O 4 [ 27 ], Co 90 Pt 10 [ 8 ], Co 75 Cr 13 Pt 12 [ 8 ], and many others. In addition to these common materials, nanotubes with more complex geometries have also been synthesized, taking into consideration factors such as diameter modulations [ 28 ], multisegmented structures [ 29 ], and core–shell [ 30 , 31 , 32 , 33 ] systems.…”
Section: Introductionmentioning
confidence: 99%